Memories of an undercover attending: Reflections on completing a second residency training. (3rd July 2019) - Sanches, Marsal
Abstract: The author, originally a full-trained psychiatrist in his home country, describes his personal experience as a resident physician in the Unites States, from a critical standpoint. The challenges and peculiarities inherent to undergoing second residency training are addressed. The singularities of the situation in question are discussed. Finally, the author provides some recommendations for teaching physicians involved in the supervision of residents, emphasizing the need for taking into consideration their trainee's respective backgrounds and their potential implications.